Artificial Intelligence-Based Islamic Education Management: Madrasah Governance Innovation in the Digital Era - Didi Kosmanto; Yusman Haris; Jenny fransiska; Idi Warsah; Jumira Warlizasusi; Eka Apriani; Destriani Destriani (Yayasan Corolla Education Centre, 2026)
The accelerating pace of digital transformation has heightened the demand for governance innovation in Islamic education institutions, particularly madrasahs striving to balance managerial effectiveness with ethical accountability. Although existing literature has explored digitalization in Islamic education, empirical research that explicitly addresses Artificial Intelligence-Based Islamic Education Management as a form of madrasah governance innovation remains limited. This study aims to investigate how AI-based Islamic education management is implemented and how it contributes to governance innovation in the digital era. A qualitative case study design was employed in selected madrasahs that have initiated digital transformation and adopted AI-supported management systems. Participants included madrasah principals, vice principals, senior teachers, academic coordinators, and information system operators who were directly involved in governance and managerial decision-making. Data were collected through semi-structured interviews, non-participant observations, and document analysis. The data were analyzed thematically to identify recurring patterns related to governance practices and innovation processes. The findings demonstrate that Artificial Intelligence-Based Islamic Education Management enhances governance effectiveness by enabling data-driven decision-making, improving administrative efficiency, and strengthening transparency and accountability in line with Islamic ethical values such as amanah and shūrā. Nevertheless, challenges related to digital literacy, infrastructure readiness, and ethical concerns regarding data use remain evident. The study implies that while AI-based management offers substantial potential for madrasah governance innovation, its sustainability depends on institutional capacity building, ethical governance frameworks, and supportive policy environments.